2002
DOI: 10.1029/2001jb000408
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic forces controlling the regional intraplate stress field in continental Australia: Results from new finite element modeling

Abstract: The tectonic forces controlling the present‐day regional intraplate stress field in continental Australia have been evaluated through a finite element analysis of the intraplate stresses in the Indo‐Australian plate (IAP). Constraint for the modeling is provided by an observed regional stress field based on observations in 12 stress provinces. A weighted “basis set” method has been employed to provide an efficient means to evaluate a very large number of tectonic force combinations and to make a quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
122
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(134 citation statements)
references
References 35 publications
12
122
0
Order By: Relevance
“…However, finite element modeling has revealed that even the complicated stress pattern observed in Australia can be accurately reproduced from plate boundary forces and intraplate sources of stress (Coblentz et al, 1998;Reynolds et al, 2002). Hence, it is likely that the complicated stress pattern observed in Southeast Asia may be accurately modelled in future studies.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…However, finite element modeling has revealed that even the complicated stress pattern observed in Australia can be accurately reproduced from plate boundary forces and intraplate sources of stress (Coblentz et al, 1998;Reynolds et al, 2002). Hence, it is likely that the complicated stress pattern observed in Southeast Asia may be accurately modelled in future studies.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…However, localized sources of stress can have a significant impact on small-scale stress patterns (Tingay et al, 2005a;Heidbach et al, 2007). Detailed analysis of the forces controlling the plate-scale and small-scale stress fields can be successfully conducted by finite element modeling (for example, Coblentz and Sandiford, 1994;Coblentz and Richardson, 1996;Gölke and Coblentz, 1996;Reynolds et al, 2002). However, such…”
Section: Regional Stress Orientations In Southeast Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that shallow processes influence both the magnitude and orientation of the lithospheric stresses. Among such processes the most important are the slab pull, ridge push, trench and continental collision (deformation) (Reynolds et al, 2002) as well as the 10 cratonic root resistance (Naliboff et al, 2012). Also, gravitational effects due to lateral density heterogeneities in the lithosphere and tractions from the mantle flow at the base of the moving plates play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Boldreel & Andersen 1993Lundin & Doré 2002;Stoker et al 2005). Studies of the origins of the present-day regional stress fields in the interiors of both the European (Gölke & Coblentz 1996) and Indo-Australasian plates (Reynolds et al 2002) using finite element analyses have shown that the state of stress at any point within the plate is a function of the net torques of all the plate boundary forces (Reynolds et al 2002). This suggests that the Neogene compressional deformation in the Irish Sea is a function of both Atlantic ridge-push forces and Alpine lithospheric shortening.…”
Section: /28-1mentioning
confidence: 99%